PENERAPAN SISTEM AKUNTANSI PERTANGGUNGJAWABAN PADA PT. POS INDONESIA (PERSERO) DI MAKASSAR - Ibrahim H. Ahmad (AkMen JURNAL ILMIAH, 2013)
This study aims to clarify the application of the accounting system to determine responsibility, as a means of controlling the PT POS Indonesia (Persero) in Makassar. This study used a descriptive approach quantitatively using comparative analysis (comparative analysis), it means comparing the practice with the theoretical framework implemented by PT POS Indonesia (Persero) in Makassar, especially with regard to the application of responsibility accounting systems. In a responsibility accounting system master budget consists of three components, namely the operating budget, capital budget, and financial budget, while the PT Pos Indonesia (Persero) Makassar only made ​​two types of budgets, the budget exploitation/load operational cost centers and revenue centers and investment budgets that support the company's investment. Reporting budget performance on PT Pos Indonesia (Persero) Makassar is a matter of accountability and valuation for managers who prepared a report on the realization of its management fee, the report includes budget realization, the realization and the deviation of each element